The effects of single-pass/double-pass technique on friction stir welding of aluminium - Nur Ain Amelia, Sathari (2013)
Friction stir welding is a solid state welding that use the idea of frictional heat to soften stirred materials without the need of melting. This study is focusing in the effects of single-pass/ double-pass technique on friction stir welding of aluminium. Two pieces aluminium alloy (AA1100) with the same thickness of 6mm were friction stir welded using CNC milling machine. Three different rotational speeds of 1400 rpm, 1600 rpm and 1800 rpm respectively were used for both groups of single-pass and double-pass. Microstructure observation of welded area was studied using metallurgy microscope. All the specimens were tested by using tensile test and Vickers hardness test to evaluate its mechanical properties. Results indicated that at low rotational speeds (rpm) due to defects such as ‘surface lack of fill’ and tunnel in the welded area contributed to the decreases the result in mechanical properties of the specimens. Welded specimens using double-pass technique shows increasing value of tensile strength and hardness value. Therefore, the optimum parameters in FSW process were double-pass technique with rotational speed of 1800 rpm.